A REVIEW OF TRADITIONAL KNOWLEDGE ON FOODS AND PLANTS SUPPOSED TO INCREASE LACTATION IN PREGNANT WOMEN: A DESCRIPTIVE STUDY - Ergol, Sule; Koc, Gulten; Kurtuncu, Meltem (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: While both the proportion of infants exclusively fed breast milk and the duration of suckling increased worldwide andin Turkey, the addition of another product to breast milk in the first six months of the infant's life is still widespread.Materials and Methods: This study was conducted as a descriptive, cross-sectional study to identify the traditional methodsintending to increase breast milk in pregnancy. The sample group consisted of 100 pregnant women in their last trimester whovisited the obstetrical outpatient clinics of a State Hospital of Zonguldak. Data were collected on a data collection form during a faceto face interview.Results: The methods for increasing lactation in pregnant women that the subjects had heard about consisted of the ingestion ofabundant water and fluid food (94.0%), green leafy vegetables (such as lettuce) (38%), sweet foods (26%) and milk or other dairyitems (19%). Of the pregnant women questioned, 19.0% declared that they would not do anything in particular to increase their milk,33% that they would drink more fluids, 14% that they would ingest apricot compost and 12% herbal teas. No significant differencesamong groups were detected between age, educational status, family type, parity and live children number on one side and thesubjects' planning to use special foods or fluids (p>0.05).Conclusion: The subjects believed that in addition to an abundant consumption of water and fluid foods, seen as essential, eatinggreen leafy vegetables, chiefly lettuce, and a particular type of sesame halva would increase lactation.